A kind of amine carbon supported aqueous sulfur-based battery positive electrode material and its preparation method and application

By adjusting the ratio of amine to sulfur carbon in the positive electrode material of the aqueous sulfur-based battery, and using solution thiamine synthesis and high-temperature melting treatment, the problem of cycle life attenuation of the aqueous sulfur-based metal battery is solved, and the long cycle performance and high-rate stability of the battery are improved.

CN118993034BActive Publication Date: 2025-03-04LUOYANG INST OF SCI & TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411437055.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-03-04
Estimated Expiration
2044-10-15

AI Technical Summary

Technical Problem

The soluble intermediate polysulfide produced by the aqueous sulfur-based metal battery after discharge is easily dissolved, resulting in a shuttle effect and attenuation of the battery cycle life. The existing solutions are costly to prepare and assemble, and the long-cycle performance improvement effect is limited.

Method used

By adjusting the ratio of amine to sulfur carbon, a solution thiamine synthesis scheme is used to form carbon-sulfur bonds on the hydrophilic carbon-based material, load the sulfur components, and perform high-temperature melting treatment under an inert atmosphere to prepare a high-stability water-based sulfur-based battery positive electrode material.

Benefits of technology

It effectively limits the dissolution of soluble intermediates generated during discharge, slows down the shuttle effect, extends the long cycle life of aqueous sulfur-based batteries, and shows excellent stability at high magnifications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118993034B_ABST
    Figure CN118993034B_ABST
Patent Text Reader

Abstract

The present invention relates to the field of electrochemical energy storage technology, specifically to an amine carbon-loaded aqueous sulfur-based battery positive electrode material and its preparation method and application, wherein an active substance is anchored by carbon-sulfur bonds on a hydrophilic carbon-based material through a solution thiamine synthesis scheme, and a sulfur component is loaded through a high-temperature melting process under an inert atmosphere to form a high-stability sulfur-based battery positive electrode material. The material can effectively limit the soluble intermediates generated during the discharge process to the positive electrode side to slow down the shuttle effect of polysulfides, thereby enhancing the long cycle life of aqueous sulfur-based batteries, and exhibits excellent rate performance in aqueous sulfur-based batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to an amine carbon-loaded aqueous sulfur-based battery positive electrode material, and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are the most widely used rechargeable battery technology in the world, and are widely used in important fields such as mobile devices, electric vehicles and energy storage. The energy density of existing lithium-ion batteries is close to the theoretical limit (about 386Wh / kg), which limits their application in many scenarios. In addition, the high cost, strict operating conditions, toxicity and flammability of organic electrolytes are also issues that cannot be ignored.

[0003] Aqueous sulfur-based metal batteries are batteries that use sulfur as the positive electrode active material, metal as the negative electrode material, and an electrolyte that is an inorganic salt aqueous solution of a certain concentration. Compared with organic lithium-ion batteries, they have the advantages of high safety, low environmental pollution, high energy density, low cost, and a wide range of raw material sources. However, the soluble intermediate polysulfide produced after discharge is severely dissolved in the aqueous electrolyte and is prone to shuttle effect, causing the battery cycle life to decay. Existing solutions mostly use high catalytic performance material modification (refer to Chinese patents with application numbers 202311845147.6 and 202410143135.7) or morphology control (refer to Chinese patents with application numbers 202410165839.4 and 202310630894.1) to extend the cycle life of sulfur-based batteries, but their preparation and assembly costs are high and the effect of improving long-cycle performance is limited. The Chinese patent with application number 201910253473.5 proposes an aqueous battery with zinc negative electrode and sulfur positive electrode, but the polarization voltage is large and the kinetics are sluggish, which cannot meet the requirements of high-rate applications. The Chinese patent with application number 202311484348.8 proposes an aqueous sulfur-manganese battery. Although the specific capacity is improved compared with the zinc-sulfur battery, the positive electrode stability is poor and stable charging and discharging at high rates and long cycles cannot be achieved. At the same time, there is still blindness in the battery design schemes such as the control of the host material structure of aqueous sulfur-based metal batteries, the electrolyte composition ratio and the selection of voltage windows, which further limits the application of aqueous sulfur-based metal batteries. Summary of the invention

[0004] To solve the above problems, the purpose of the present invention is to provide an amine-carbon loaded aqueous sulfur-based battery positive electrode material and its preparation method and application, by adjusting the ratio of amine to sulfur-carbon, weakening the shuttle effect caused by the dissolution of soluble polysulfides generated by discharge, so as to extend the long cycle performance of aqueous sulfur-based batteries.

[0005] The present invention provides a method for preparing an amine carbon-loaded aqueous sulfur-based battery positive electrode material, which specifically comprises the following steps:

[0006] (1) Pretreatment of carbon-based materials

[0007] The mixed acid is added into the reaction kettle, and the carbon-based material is dissolved in the mixed acid for treatment to remove impurities on the surface of the carbon-based material and improve its hydrophilicity, thereby obtaining the pretreated carbon-based material.

[0008] (2) Preparation of water-dispersible carbon-based materials

[0009] The pretreated carbon-based material is placed in deionized water and ultrasonically oscillated. During the ultrasonic oscillation, a non-ionic surfactant is slowly added while oscillating. After the ultrasonic oscillation is completed, a uniformly dispersed water-dispersible carbon-based material dispersion is obtained.

[0010] (3) Preparation of sulfur-modified carbon-based materials

[0011] The sublimated sulfur powder, the amine compound, the hydrochloric acid and the carbon-based material dispersion obtained in step (2) are mixed and reacted, the solution obtained by the reaction is filtered, and then the solid matter obtained by filtration is washed with deionized water and vacuum dried to obtain the sulfur-modified carbon-based material.

[0012] (4) Preparation of amine carbon-loaded aqueous sulfur-based battery cathode materials

[0013] The sulfur-modified carbon-based material obtained in step (3) and the sublimated sulfur powder are mixed in a mass ratio of 4:6, and a solvent is added for liquid phase grinding. The ground mixture is loaded into a porcelain boat, and the porcelain boat is placed in a tubular furnace filled with an inert atmosphere, and the temperature is raised to 150-160° C. and calcined at this temperature. After the calcination is completed, it is naturally cooled to room temperature to obtain an amine carbon-loaded aqueous sulfur-based battery positive electrode material.

[0014] Furthermore, the carbon-based material in step (1) is one of graphene and carbon nanotubes.

[0015] Furthermore, the mixed acid in step (1) is obtained by mixing concentrated hydrochloric acid and concentrated nitric acid.

[0016] Furthermore, in step (1), the carbon-based material is dissolved in mixed acid for treatment. Specifically, the carbon-based material is dissolved in mixed acid, and then the reactor is transferred to a drying oven at 180° C. and acidified for 12 hours. After the acidification is completed, the solution obtained after acidification is naturally cooled to room temperature, and the upper liquid is discarded. The obtained precipitate is washed with deionized water and anhydrous ethanol, and then vacuum dried at 60° C. for 12 hours to obtain the pretreated carbon-based material;

[0017] Furthermore, in step (2), the nonionic surfactant is one of N-methylpyrrolidone, polyoxyethylene ether, and propylene glycol monofatty acid ester.

[0018] Furthermore, in step (3), the amine compound is N,N-dimethylformamide, melamine or ethylenediamine.

[0019] Furthermore, when the amine compound in step (3) is N,N-dimethylformamide or ethylenediamine, step (3) specifically comprises dissolving sublimated sulfur powder in N,N-dimethylformamide or ethylenediamine to obtain solution A, slowly dripping solution A into the carbon-based material dispersion obtained in step (2) at room temperature in three portions, ultrasonically oscillating while dripping, each ultrasonic oscillation lasting 30 minutes, and dripping hydrochloric acid after each ultrasonic oscillation. After all the dripping is completed, ultrasonication is continued for 30 minutes to ensure uniform mixing. After the ultrasonication is completed, the obtained solution is filtered, and then the solid matter obtained by filtration is washed with deionized water and vacuum dried to obtain the sulfur-modified carbon-based material.

[0020] Furthermore, when the amine compound in step (3) is melamine, step (3) specifically comprises: slowly adding melamine to a portion of hydrochloric acid with a mass fraction of 10 wt.%, and ultrasonically oscillating for 1 hour to obtain an amine dispersion; slowly dripping the above amine dispersion into the carbon-based material dispersion obtained in step (2), while ultrasonically oscillating during the dripping, to obtain solution B after the dripping is completed; then dissolving the sublimated sulfur powder in solution B, and slowly dripping another portion of hydrochloric acid into solution B three times, ultrasonically oscillating for 30 minutes, after the ultrasonication is completed, filtering the obtained solution, and then washing the solid matter obtained by filtration with deionized water, and vacuum drying to obtain the sulfur-modified carbon-based material.

[0021] Furthermore, in step (3), the mass ratio of sublimated sulfur powder to amine compound is 5-70:1.

[0022] Furthermore, in step (3), the temperature of the vacuum drying oven is 60-70°C.

[0023] Furthermore, the solvent added in the liquid phase grinding in step (4) is anhydrous ethanol; the inert atmosphere is argon, the temperature is increased to 150-160°C at a heating rate of 2°C / min, and the temperature is maintained for 10-12 hours for calcination.

[0024] The present invention also provides an amine carbon-loaded aqueous sulfur-based battery positive electrode material obtained according to the above preparation method and application of the amine carbon-loaded aqueous sulfur-based battery positive electrode material in an aqueous sulfur-based battery.

[0025] Furthermore, the application of the amine carbon-loaded aqueous sulfur-based battery positive electrode material in an aqueous sulfur-based battery is specifically to mix the amine carbon-loaded aqueous sulfur-based battery positive electrode material, a conductive agent, and a binder in a mass ratio of 8:1:1, add deionized water as a solvent, grind until the slurry is uniform, apply it on a current collector, and obtain a battery positive electrode after drying, and assemble the positive electrode with a separator and a metal negative electrode into a button battery.

[0026] Furthermore, in the application of the amine carbon-loaded aqueous sulfur-based battery positive electrode material in aqueous sulfur-based batteries, the conductive agent is Super P or Ketjen black; the binder is sodium carboxymethyl cellulose or sodium alginate; the diaphragm material is glass fiber; and the metal negative electrode is a copper sheet or a zinc sheet.

[0027] Compared with the prior art, the present invention has the following beneficial effects:

[0028] The present invention uses a solution thiamine synthesis scheme to anchor the active substance on the hydrophilic carbon-based material with a carbon-sulfur bond, and undergoes a high-temperature melting process under an inert atmosphere to load the sulfur component to form a high-stability aqueous sulfur-based battery positive electrode material. The material can effectively limit the soluble intermediates generated during the discharge process to the positive electrode side to slow down the shuttle effect of polysulfides, thereby enhancing the long cycle life of the aqueous sulfur-based battery, and exhibits excellent rate performance in the aqueous sulfur-based battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 is a SEM image of the amine carbon-supported aqueous sulfur-based battery positive electrode material prepared in Example 1;

[0030] Figure 2 is the XRD pattern of the amine carbon-supported aqueous sulfur-based battery positive electrode material prepared in Example 1;

[0031] Figure 3 is the Raman graph of the amine carbon-supported aqueous sulfur-based battery cathode material prepared in Example 1;

[0032] Figure 4 This is the BET diagram of the amine carbon-supported aqueous sulfur-based battery cathode material prepared in Example 1;

[0033] Figure 5 is a TGA graph of the amine carbon-supported aqueous sulfur-based battery positive electrode material prepared in Example 1;

[0034] Figure 6 This is a rate performance diagram of a button cell assembled with the amine carbon-supported aqueous sulfur-based battery positive electrode material prepared in Example 1;

[0035] Figure 7 1 is a charge and discharge curve diagram of a button cell assembled from the amine carbon-supported aqueous sulfur-based battery positive electrode material prepared in Example 1 at different rates;

[0036] Figure 8 The button cell assembled from the amine carbon-supported aqueous sulfur-based battery cathode material prepared in Example 1 was 5 Ag -1 Cyclic curves measured at a current density of ;

[0037] Fig. 9The button cell assembled from the carbon-supported aqueous sulfur-based battery cathode material prepared in Comparative Example 1 was 5 Ag -1 Cyclic curves measured at a current density of . DETAILED DESCRIPTION

[0038] In order to better understand the content of the present invention, the present invention will be further described below in conjunction with specific embodiments and drawings. The following embodiments are implemented based on the technology of the present invention, and detailed implementation methods and operating steps are given, but the protection scope of the present invention is not limited to the following embodiments.

[0039] Embodiment 1:

[0040] (1) Mix 25 mL of concentrated hydrochloric acid and 10 mL of concentrated nitric acid to obtain a mixed acid, add the mixed acid into a reactor, dissolve 100 mg of graphene in the mixed acid, transfer the reactor to a drying oven at 180° C., acidify for 12 h, cool naturally to room temperature after the acidification, centrifuge the solution obtained after acidification, discard the upper liquid, wash the obtained precipitate with deionized water and anhydrous ethanol, and vacuum dry at 60° C. for 12 h to obtain a carboxylated few-layer graphene material;

[0041] (2) placing the carboxylated few-layer graphene material prepared in step (1) in 100 mL of deionized water and ultrasonically oscillating for 1.5 h. During the ultrasonic oscillation, 5 mL of N-methylpyrrolidone was slowly added dropwise while oscillating. After the ultrasonic oscillation, a uniformly dispersed black carbon-based material dispersion was obtained.

[0042] (3) Dissolve 400 mg of sublimed sulfur powder in 80 mg of ethylenediamine to obtain solution A, and slowly drip solution A into the carbon-based material dispersion obtained in step (2) at room temperature in three portions, while ultrasonically oscillating the solution, each time for 30 min, and after each ultrasonic oscillation, drip 10 wt.% HCl solution, the total volume of the HCl solution is 140 mL. After all the additions are completed, continue ultrasonication for 30 min to ensure uniform mixing. After the ultrasonication is completed, filter the obtained solution by suction, wash the solid matter obtained by suction with deionized water, and dry it in a vacuum drying oven at 60°C for 18 h to obtain a sulfur-modified carbon-based material;

[0043] (4) Weigh 80 mg of the sulfur-modified carbon-based material obtained in step (3), mix it with sublimated sulfur powder in a mass ratio of 4:6, then add 3 mL of anhydrous ethanol and grind it thoroughly. Put the mixture obtained after grinding into a porcelain boat and place the porcelain boat in a tubular furnace filled with Ar gas. Raise the temperature to 155°C at a heating rate of 2°C / min and keep it at this temperature for 12 hours. After the insulation is completed, naturally cool it to room temperature to finally obtain an amine carbon-supported aqueous sulfur-based battery positive electrode material;

[0044] The amine carbon-loaded aqueous sulfur-based battery positive electrode material prepared in Example 1 was fully mixed with the conductive agent Super P and the binder sodium carboxymethyl cellulose in a mass ratio of 8:1:1, and 5 mL of deionized water was dropped into the mixture for grinding and dispersion to obtain a paint-like uniform slurry, which was evenly distributed on a copper foil with a diameter of 12 mm by manual coating and dried at 60°C for 12 h. After drying, the copper foil coated with the amine carbon-loaded aqueous sulfur-based battery positive electrode material was used as the positive electrode, Celgard 2400 glass fiber was used as the diaphragm, and the copper sheet was used as the counter electrode. The slurry was stirred for 2 hours at a concentration of 0.5 mol L -1 The CuSO4 solution was used as the battery electrolyte to assemble a button battery and allowed to stand at room temperature for 8 h. The resulting battery was an aqueous copper-sulfur battery.

[0045] Figure 1 This is the SEM image of the amine carbon-supported aqueous sulfur-based battery cathode material prepared in Example 1. Figure 1 It can be seen that the graphene nanolayer structure is complete and can serve as an excellent electron carrier in the charge and discharge reaction process. The graphene nanolayer has an obvious curling tendency. This is because under the action of ethylenediamine solution, the sulfur molecules attached to the surface of the graphene produce high surface tension, which makes the edges of the graphene nanolayer wrinkle, forming a three-dimensional conductive structure, which can not only serve as a conductive carrier, but also can fully accommodate the active substance sulfur.

[0046] Figure 2 The XRD pattern of the amine carbon-supported aqueous sulfur-based battery cathode material prepared in Example 1 is shown in FIG. Figure 2 The diffraction peaks of orthorhombic S8 molecules can be identified, indicating that it has good crystallinity.

[0047] Figure 3 The Raman diagram of the amine carbon-supported aqueous sulfur-based battery cathode material prepared in Example 1 is shown in FIG. Figure 3 It can be seen that at 1346 cm -1 and 1580 cm -1 The D and G peaks of carbon materials are related to the defects of carbon atom crystals, while the G peak represents the sp 2 For the hybrid in-plane stretching vibration, the intensity ratio of the D peak to the G peak was calculated to be 1.10 (ID / IG), indicating that the prepared composite material has a high degree of graphitization. The carbon materials all have partial defects. The material defects can effectively increase the reaction binding sites of the sulfur component, and the degree of graphitization is also high, which also provides evidence for the high electronic conductivity of the carbon substrate.

[0048] Figure 4 The BET diagram of the amine carbon-supported aqueous sulfur-based battery cathode material prepared in Example 1 is shown in FIG. Figure 4It can be seen that the material has a suitable specific surface area, and the micro-mesoporous structure can not only store the active sulfur component, but also effectively limit the escape of polysulfides, thereby inhibiting the shuttling effect of polysulfides through physical confinement.

[0049] Figure 5 This is the TGA diagram of the amine carbon-supported aqueous sulfur-based battery positive electrode material prepared in Example 1. Figure 5 It can be seen that the sulfur content in the material is 51 wt.%.

[0050] Figure 6 The rate performance diagram of the button cell assembled with the amine carbon-supported aqueous sulfur-based battery positive electrode material prepared in Example 1 is shown at 2.5, 5.0, 7.5, 10.0, 12.5, and 15.0 A g -1 It has excellent discharge capacity at current density. When the current density is restored to 2.5 A g -1 After that, the reversible capacity can be restored to its initial value, which shows that its structure has good stability and can output current quickly with good consistency under different current density changes.

[0051] Figure 7 The charge and discharge curves of the button battery assembled with the amine carbon-supported aqueous sulfur-based battery positive electrode material prepared in Example 1 at different rates are shown in FIG. Figure 7 It can be concluded that its polarization voltage is small.

[0052] Figure 8 The button cell assembled with the amine carbon-supported aqueous sulfur-based battery cathode material prepared in Example 1 was 5 Ag -1 The cycle curves measured at a current density of 5A g -1 The initial reversible capacity at this current density is 1853 mAhg -1 After 300 cycles, the discharge capacity is still as high as 1630 mAh g -1 The average capacity decay rate per cycle is only 0.04%, indicating that the amine carbon-loaded aqueous sulfur-based battery positive electrode material enables the aqueous sulfur-based battery to exhibit excellent cycle stability.

[0053] Embodiment 2:

[0054] (1) Mix 25 mL of concentrated hydrochloric acid and 10 mL of concentrated nitric acid to obtain a mixed acid, add the mixed acid into a reactor, dissolve 100 mg of carbon nanotubes in the mixed acid, and then transfer the reactor to a drying oven at 180°C for acidification for 12 h. After the acidification is completed, naturally cool to room temperature, centrifuge the solution obtained after acidification, discard the upper liquid, wash the obtained precipitate with deionized water and anhydrous ethanol, and vacuum dry it at 60°C for 12 h to obtain carboxylated carbon nanotubes;

[0055] (2) placing the carboxylated carbon nanotubes prepared in step (1) in 100 mL of deionized water and ultrasonically vibrating the water for 1.5 h. During the ultrasonic vibration, 2.5 mL of polyoxyethylene ether was slowly added dropwise while the ultrasonic vibration was completed. After the ultrasonic vibration was completed, a uniformly dispersed black carbon-based material dispersion was obtained.

[0056] (3) 400 mg of sublimed sulfur powder was dissolved in 80 mg of N,N-dimethylformamide to obtain solution A, and solution A was slowly dripped into the carbon-based material dispersion obtained in step (2) at room temperature in three portions, with ultrasonic oscillation during the dripping, each ultrasonic oscillation lasting 30 min, and after each ultrasonic oscillation, 10 wt.% HCl solution was dripped, with a total volume of 140 mL of HCl solution. After all the dripping was completed, ultrasonication was continued for 30 min to ensure uniform mixing. After the ultrasonication was completed, the obtained solution was filtered, and the solid matter obtained by filtration was washed with deionized water, and then dried in a vacuum drying oven at 60°C for 18 h to obtain a sulfur-modified carbon-based material;

[0057] (4) Weigh 80 mg of the sulfur-modified carbon-based material obtained in step (3), mix it with sublimated sulfur powder in a mass ratio of 4:6, then add 3 mL of anhydrous ethanol and grind it thoroughly. Put the mixture obtained after grinding into a porcelain boat and place the porcelain boat in a tubular furnace filled with Ar gas. Raise the temperature to 155°C at a heating rate of 2°C / min and keep it at this temperature for 12 hours. After the insulation is completed, naturally cool it to room temperature to finally obtain an amine carbon-supported aqueous sulfur-based battery positive electrode material;

[0058] The amine carbon-loaded aqueous sulfur-based battery positive electrode material prepared in Example 2 was fully mixed with the conductive agent Ketjen black and the binder sodium alginate in a mass ratio of 8:1:1, and 5 mL of deionized water was dropped into the mixture for grinding and dispersion to obtain a paint-like uniform slurry, which was evenly distributed on a copper foil with a diameter of 12 mm by manual coating and dried at 60°C for 12 h. After drying, the copper foil coated with the amine carbon-loaded aqueous sulfur-based battery positive electrode material was used as the positive electrode, Celgard 2400 glass fiber was used as the diaphragm, and the copper sheet was used as the counter electrode. The slurry was stirred for 2 hours at a concentration of 0.5 mol L -1 The CuSO4 solution was used as the battery electrolyte, assembled into a button battery, and left to stand at room temperature for 8 h.

[0059] Embodiment 3:

[0060] (1) Mix 25 mL of concentrated hydrochloric acid and 10 mL of concentrated nitric acid to obtain a mixed acid, add the mixed acid into a reactor, dissolve 100 mg of carbon nanotubes in the mixed acid, and then transfer the reactor to a drying oven at 180°C for acidification for 12 h. After the acidification is completed, naturally cool to room temperature, centrifuge the solution obtained after acidification, discard the upper liquid, wash the obtained precipitate with deionized water and anhydrous ethanol, and vacuum dry it at 60°C for 12 h to obtain carboxylated carbon nanotubes;

[0061] (2) placing the carboxylated carbon nanotubes prepared in step (1) in 100 mL of deionized water and subjecting them to ultrasonic oscillation for 1.5 h. During the ultrasonic oscillation, slowly adding 2.5 mL of propylene glycol monofatty acid ester while oscillating. After the ultrasonic oscillation, a uniformly dispersed black carbon-based material dispersion is obtained.

[0062] (3) Slowly add 10 mg of melamine to 100 mL of 10 wt.% HCl solution, and ultrasonically vibrate for 1 hour to obtain an amine dispersion. Slowly drip the above amine dispersion into the carbon-based material dispersion obtained in step (2), while ultrasonically vibrating. After the dripping is completed, solution B is obtained, and then 50 mg of sublimated sulfur powder is dissolved in solution B, and 40 mL of 10 wt.% HCl solution is slowly dripped into solution B three times, and ultrasonically vibrated for 30 minutes. After the ultrasonication is completed, the obtained solution is filtered, and then the solid matter obtained by filtration is washed with deionized water, and then placed in a vacuum drying oven at 60°C for 18 hours to obtain a sulfur-modified carbon-based material;

[0063] (4) Weigh 80 mg of the sulfur-modified carbon-based material obtained in step (3), mix it with sublimated sulfur powder in a mass ratio of 4:6, then add 3 mL of anhydrous ethanol and grind it thoroughly. Put the mixture obtained after grinding into a porcelain boat and place the porcelain boat in a tubular furnace filled with Ar gas. Raise the temperature to 155°C at a heating rate of 2°C / min and keep it at this temperature for 12 hours. After the insulation is completed, naturally cool it to room temperature to finally obtain an amine carbon-supported aqueous sulfur-based battery positive electrode material;

[0064] The amine carbon-loaded aqueous sulfur-based battery positive electrode material prepared in Example 3 was fully mixed with the conductive agent Ketjen black and the binder sodium alginate in a mass ratio of 8:1:1, and 5 mL of deionized water was dropped into the mixture for grinding and dispersion to obtain a paint-like uniform slurry, which was evenly distributed on a copper foil with a diameter of 12 mm by manual coating and dried at 60°C for 12 h. After drying, the copper foil coated with the amine carbon-loaded aqueous sulfur-based battery positive electrode material was used as the positive electrode, Celgard 2400 glass fiber was used as the diaphragm, and the copper sheet was used as the counter electrode. The slurry was stirred for 2 hours at a concentration of 0.5 mol L -1 The CuSO4 solution was used as the battery electrolyte, assembled into a button battery, and left to stand at room temperature for 8 h.

[0065] In other embodiments, the prepared amine carbon-supported aqueous sulfur-based battery positive electrode material can be used in aqueous sulfur-based batteries, and the aqueous sulfur-based batteries include but are not limited to aqueous copper-sulfur batteries.

[0066] Embodiment 4:

[0067] (1) Same as step (1) in Example 1;

[0068] (2) Same as step (2) in Example 1;

[0069] (3) Dissolve 700 mg of sublimed sulfur powder in 10 mg of ethylenediamine to obtain solution A, and slowly drip solution A into the carbon-based material dispersion obtained in step (2) at room temperature in three portions, while ultrasonically oscillating for 30 min each time, and after each ultrasonic oscillation, drip 10 wt.% HCl solution, the total volume of the HCl solution is 140 mL. After all the additions are completed, continue ultrasonication for 30 min to ensure uniform mixing. After the ultrasonication is completed, filter the obtained solution by suction, wash the solid matter obtained by suction with deionized water, and dry it in a vacuum drying oven at 70°C for 18 h to obtain a sulfur-modified carbon-based material;

[0070] (4) Weigh 80 mg of the sulfur-modified carbon-based material obtained in step (3), mix it with sublimated sulfur powder in a mass ratio of 4:6, then add 3 mL of anhydrous ethanol and grind it thoroughly. Put the mixture obtained after grinding into a porcelain boat and place the porcelain boat in a tubular furnace filled with Ar gas. Raise the temperature to 160°C at a heating rate of 2°C / min and keep it at this temperature for 10 hours. After the insulation is completed, naturally cool it to room temperature to finally obtain an amine carbon-supported aqueous sulfur-based battery positive electrode material;

[0071] The amine carbon-loaded aqueous sulfur-based battery positive electrode material prepared in Example 4 was fully mixed with the conductive agent Ketjen black and the binder sodium alginate in a mass ratio of 8:1:1, and 5 mL of deionized water was dropped into the mixture for grinding and dispersion to obtain a paint-like uniform slurry, which was evenly distributed on a 100-mesh titanium mesh by manual coating and dried at 60°C for 12 h. After drying, the titanium mesh coated with the amine carbon-loaded aqueous sulfur-based battery positive electrode material was used as the positive electrode, Celgard 2400 glass fiber was used as the diaphragm, and the zinc sheet was used as the counter electrode. The slurry was stirred for 2 hours at a concentration of 0.5 mol L -1 The ZnCl2 solution was used as the battery electrolyte to assemble a button battery and allowed to stand at room temperature for 8 h. The resulting battery was an aqueous zinc-sulfur battery.

[0072] Comparative Example 1:

[0073] (1) Same as step (1) in Example 1;

[0074] (2) Same as step (2) in Example 1;

[0075] (3) Filtering the carbon-based material dispersion obtained in step (2), then washing the solid matter obtained by filtration with deionized water, and drying it in a vacuum drying oven at 60° C. for 18 h to obtain a carbon-based material;

[0076] (4) Weigh 80 mg of the carbon-based material obtained in step (3), mix it with sublimated sulfur powder in a mass ratio of 4:6, then add 3 mL of anhydrous ethanol and grind it thoroughly. Put the mixture obtained after grinding into a porcelain boat and place the porcelain boat in a tubular furnace filled with Ar gas. Raise the temperature to 155°C at a heating rate of 2°C / min and keep it at this temperature for 12 hours. After the insulation is completed, naturally cool it to room temperature to finally obtain a carbon-supported aqueous sulfur-based battery positive electrode material;

[0077] According to the method for preparing button batteries using the amine carbon-loaded aqueous sulfur-based battery positive electrode material obtained in Example 1, the amine carbon-loaded aqueous sulfur-based battery positive electrode material obtained in Example 1 is replaced with the carbon-loaded aqueous sulfur-based battery positive electrode material obtained in Comparative Example 1 to prepare button batteries.

[0078] Fig. 9 The button cell prepared from the carbon-supported aqueous sulfur-based battery positive electrode material obtained in Comparative Example 1 was -1 The cycle curve measured at a current density of 1.5 200 mAh g -1 , which is lower than the initial reversible specific capacity of Example 1 (the initial reversible capacity in Example 1 is 1853 mAh g -1 ), and the capacity decay is serious after 50 cycles, which shows that the amine carbon-loaded aqueous sulfur-based battery positive electrode material prepared by the solution thiamine-high temperature melting method can effectively increase the sulfur storage active sites, can make the sulfur component evenly dispersed on the electrode surface, and effectively inhibit the shuttle effect of soluble intermediates generated during the discharge process through carbon-sulfur chemical bonding, resulting in a significant improvement in battery stability. However, the capacity and stability of the sample prepared by the direct high temperature melting method in Comparative Example 1 are relatively poor.

[0079] The above is only an embodiment of the present invention, and does not limit the present invention in any form. The present invention can also have other forms of embodiments according to the above structures and functions, which are not listed one by one. Therefore, any simple modification, equivalent change and modification made by any technician familiar with the profession to the above embodiment according to the technical essence of the present invention without departing from the scope of the technical solution of the present invention still falls within the scope of the technical solution of the present invention.

Claims

1. A method for preparing an amine carbon-supported aqueous sulfur-based battery positive electrode material, characterized in that: The specific steps include: (1) Pretreatment of carbon-based materials Adding a mixed acid into a reaction kettle, and then dissolving a carbon-based material in the mixed acid for treatment to obtain a pretreated carbon-based material; the carbon-based material is one of graphene and carbon nanotubes; (2) Preparation of water-dispersible carbon-based materials The pretreated carbon-based material is placed in deionized water and subjected to ultrasonic oscillation. During the ultrasonic oscillation, a non-ionic surfactant is slowly added dropwise while oscillating. After the ultrasonic oscillation is completed, a uniformly dispersed carbon-based material dispersion is obtained; (3) Preparation of sulfur-modified carbon-based materials The sublimated sulfur powder, the amine compound, hydrochloric acid and the carbon-based material dispersion obtained in step (2) are mixed and reacted, the solution obtained by the reaction is filtered, and the solid matter obtained by filtration is washed with deionized water and vacuum dried to obtain a sulfur-modified carbon-based material; the amine compound is N,N-dimethylformamide, melamine or ethylenediamine, and the mass ratio of the sublimated sulfur powder to the amine compound is 5-70:1; When the amine compound in step (3) is melamine, step (3) specifically comprises: slowly adding melamine to a portion of hydrochloric acid with a mass fraction of 10 wt.%, and ultrasonically oscillating for 1 hour to obtain an amine dispersion; slowly dripping the above amine dispersion into the carbon-based material dispersion obtained in step (2), ultrasonically oscillating while dripping, and obtaining solution B after the dripping is completed; then dissolving sublimated sulfur powder in solution B, and slowly dripping another portion of hydrochloric acid into solution B three times, ultrasonically oscillating for 30 minutes, and after the ultrasonication is completed, filtering the obtained solution, and then washing the solid matter obtained by filtration with deionized water, and vacuum drying at 60-70° C. to obtain the sulfur-modified carbon-based material; (4) Preparation of amine carbon-loaded aqueous sulfur-based battery cathode materials The sulfur-modified carbon-based material obtained in step (3) and the sublimated sulfur powder are mixed in a mass ratio of 4:6, and a solvent is added for liquid phase grinding. The ground mixture is loaded into a porcelain boat and the porcelain boat is placed in a tubular furnace filled with argon atmosphere. The temperature is increased to 150-160°C at a heating rate of 2°C / min and kept at this temperature for 10-12h for calcination. After the calcination is completed, it is naturally cooled to room temperature to obtain an amine carbon-loaded aqueous sulfur-based battery positive electrode material.

2. The method for preparing the amine carbon-supported aqueous sulfur-based battery positive electrode material according to claim 1, characterized in that: The mixed acid in step (1) is obtained by mixing concentrated hydrochloric acid and concentrated nitric acid; the non-ionic surfactant in step (2) is one of N-methylpyrrolidone, polyoxyethylene ether, and propylene glycol monofatty acid ester.

3. The method for preparing the amine carbon-supported aqueous sulfur-based battery positive electrode material according to claim 1, characterized in that: In step (1), the carbon-based material is dissolved in mixed acid for treatment. Specifically, the carbon-based material is dissolved in mixed acid, and then the reactor is transferred to a drying oven at 180° C. and acidified for 12 hours. After the acidification is completed, it is naturally cooled to room temperature, the solution obtained after acidification is centrifuged, the upper liquid is discarded, and the obtained precipitate is washed with deionized water and anhydrous ethanol, and then vacuum dried at 60° C. for 12 hours to obtain the pretreated carbon-based material.

4. The method for preparing the amine carbon-supported aqueous sulfur-based battery positive electrode material according to claim 1, characterized in that: When the amine compound in step (3) is N,N-dimethylformamide or ethylenediamine, step (3) specifically comprises dissolving sublimated sulfur powder in N,N-dimethylformamide or ethylenediamine to obtain solution A, slowly dripping solution A into the carbon-based material dispersion obtained in step (2) at room temperature in three portions, ultrasonically oscillating while dripping, each ultrasonic oscillation lasting 30 minutes, and dripping hydrochloric acid after each ultrasonic oscillation. After all the dripping is completed, ultrasonication is continued for 30 minutes to ensure uniform mixing. After the ultrasonication is completed, the obtained solution is filtered by suction, and the solid matter obtained by suction filtration is washed with deionized water and then dried in a vacuum at 60-70° C. to obtain the sulfur-modified carbon-based material.

5. The method for preparing the amine carbon-supported aqueous sulfur-based battery positive electrode material according to claim 1, characterized in that: The solvent added in the liquid phase grinding in step (4) is anhydrous ethanol.

6. The amine carbon-supported aqueous sulfur-based battery positive electrode material obtained by the preparation method according to any one of claims 1 to 5.

7. Use of the amine carbon-supported aqueous sulfur-based battery positive electrode material as claimed in claim 6 in aqueous sulfur-based batteries.

8. The use of the amine carbon-supported aqueous sulfur-based battery positive electrode material in an aqueous sulfur-based battery as claimed in claim 7, characterized in that: Specifically, the amine carbon-loaded aqueous sulfur-based battery positive electrode material, conductive agent, and binder are mixed in a mass ratio of 8:1:1, deionized water is added as a solvent, ground until the slurry is uniform, coated on the current collector, and dried to obtain the battery positive electrode, which is assembled into a button battery with a separator and a metal negative electrode.

9. The use of the amine carbon-supported aqueous sulfur-based battery positive electrode material as claimed in claim 8 in an aqueous sulfur-based battery, characterized in that: The conductive agent is Super P or Ketjen Black; the binder is sodium carboxymethyl cellulose or sodium alginate; the separator material is glass fiber; and the metal negative electrode is a copper sheet or a zinc sheet.

Citation Information

Patent Citations

  • Cathode material for zinc-based battery based on aqueous solution and preparation and application thereof

    CN109888254A

  • Preparation method of nano flower-shaped vulcanized polyacrylonitrile material and application of nano flower-shaped vulcanized polyacrylonitrile material in battery

    CN116891545A

  • Positive electrode material modified with iron nanoparticles and preparation method thereof, and sodium-sulfur battery

    CN117497765B

  • Rechargeable aqueous sulfur-manganese battery

    CN117497880A

  • Biomass amorphous porous carbon material and room-temperature sodium-sulfur battery positive electrode material

    CN117945401A